Pengaruh Kualitas Produk, Citra Perusahaan dan Harga Terhadap Keputusan Pembelian Produk Minuman Beralkohol Selama Pandemi Covid 19 - Erynayati, Luh; Krisyanti, Ni Putu (Rifa'Institute, 2022)
In implementing marketing ideas, companies need to look at the variables that can influence purchasing decisions in promoting a product. This exploration is directed to find out how the description of PT. Trisno Mitra Bali, which is well-known among drink lovers, the quality of the products provided, along with the prices given influence purchasing decisions during the covid 19 pandemic. The population in this study were customers of PT. Trisno Mitra Bali Denpasar. The sample was determined by a purposive examination strategy, with 100 respondents. Information selection procedure used is a questionnaire. The scientific method used in this exploration is instrument test (validity test and reliability test), classical assumption test, multiple linear regression analysis, coefficient of determination, hypothesis testing (t test and F test) involving the SPSS 25 for windows program.The results show that product quality, company image, and results at the same time influence purchasing decisions.